A diffusion model approach to analyzing performance on the Flanker task: The role of the DLPFC. Issue 5 (November 2019) - SOARES, SERGIO MIGUEL PEREIRA; ONG, GABRIEL; ABUTALEBI, JUBIN; DEL MASCHIO, NICOLA; SEWELL, DAVID; WEEKES, BRENDAN
Abstract : The anterior cingulate cortex (ACC) and the dorsolateral prefrontal cortex (DLPFC) are involved in conflict detection and conflict resolution, respectively. Here, we investigate how lifelong bilingualism induces neuroplasticity to these structures by employing a novel analysis of behavioural performance. We correlated grey matter volume (GMV) in seniors reported by Abutalebi et al. (2015) with behavioral Flanker task performance fitted using the diffusion model (Ratcliff, 1978). As predicted, we observed significant correlations between GMV in the DLPFC and Flanker performance. However, for monolinguals the non-decision time parameter was significantly correlated with GMV in the left DLPFC, whereas for bilinguals the correlation was significant in the right DLPFC. We also found a significant correlation between age and GMV in left DLPFC and the non-decision time parameter for the conflict effect for monolinguals only. We submit that this is due to cumulative demands on cognitive control over a lifetime of bilingual language processing.